Organizing pneumonia as presenting feature of primary Sjögren's syndrome: A case report. (2023) - Fernandez-Trujillo, Liliana; Morales, Eliana I.; Arias, Daniela; Zúñiga-Restrepo, Valeria; Sua, Luz F.
Abstract: Sjögren's Syndrome (SS) is an autoimmune inflammatory disease, characterized by lymphocytic infiltration of exocrine glands. Approximately 10% of patients with SS have pulmonary involvement as the first manifestation of their disease, the most common being non-specific interstitial pneumonia. We present the case of a 51-year-old man with organizing pneumonia as the presenting feature of primary SS. Pulmonary involvement as the presenting feature of SS is uncommon, especially when the pattern on CT-scan is that of organized pneumonia. Initial management includes steroids and other immunosuppressants agents, with a better response in organized pneumonia secondary SS cases.